Considerarion of Superatomic Hibrid Orbital in superatom M@Al12 (M = Be, Mg, Ca, Sr). Issue 1 (April 2020) - Toba, Teruyuki; Yamasaki, Masaya; Ishii, Tomohiko; Sakane, Genta
Abstract: We introduce a superatom, which is regarded as a modern alchemy and has been studied around the world. The superatom is a nanocluster composed of multiple atoms, for example Al13 . Very interestingly, the "superatom" can mimic the chemical properties of "atom", for example, the superatom Al13 exhibits the character of halogen atom, such as Cl. If this superatom is synthesized to an appropriate size freely, there is the possibility to be placed as an "artificial atom" in a three-dimensional periodic table, such as the conventional two-dimensional periodic table. In recent years, the exhaustion of rare metals has become a big problem, so that in the next generation of materials and devices, the superatom play as an important role, and it is expected to be used for various materials or as a substitute for expensive metal catalysts such as Pt. From these points of view, the superatom have been studied all over the world up to now, but there is not much studies on their electronic structures. Therefore, in this study, we have analyzed the electronic states of the chalcogen-encapsulated type superatom M@Al12 (M = Be, Mg, Ca, Sr) by means of DV-Xα molecular orbital calculation. Our research revealed that the electronic configuration of the superatom, which changed only the central atom, depends largely on the kind of doped atom. And we can also confirm the "superatomic hybrid orbitals (SAHOs)" composed of superatomic orbitals (SAOs), and chalcogen characteristics.